EM-Based Channel Estimation Algorithms for OFDM - Ma Xiaoqiang; Kobayashi Hisashi; Schwartz Stuart C (EURASIP Journal on Advances in Signal Processing, 2004)
Estimating a channel that is subject to frequency-selective Rayleigh fading is a challenging problem in an orthogonal frequency division multiplexing (OFDM) system. We propose three EM-based algorithms to efficiently estimate the channel impulse response (CIR) or channel frequency response of such a system operating on a channel with multipath fading and additive white Gaussian noise (AWGN). These algorithms are capable of improving the channel estimate by making use of a modest number of pilot tones or using the channel estimate of the previous frame to obtain the initial estimate for the iterative procedure. Simulation results show that the bit error rate (BER) as well as the mean square error (MSE) of the channel can be significantly reduced by these algorithms. We present simulation results to compare these algorithms on the basis of their performance and rate of convergence. We also derive Cramer-Rao-like lower bounds for the unbiased channel estimate, which can be achieved via these EM-based algorithms. It is shown that the convergence rate of two of the algorithms is independent of the length of the multipath spread. One of them also converges most rapidly and has the smallest overall computational burden.